EDUCATION, UNIVERSITY, AND STUDENT MOVEMENTS IN THE HISTORY OF LATIN AMERICA: SOME CONSIDERATIONS ON THE HISTORIOGRAPHY OF THE 20TH AND 21ST CENTURIES - Toro Blanco, Pablo Andrés; Dip, Nicolás; Álvarez, Ana Lucía (Historia y Memoria de la Educación, 2024)
This text presents two views of the university phenomenon in Latin America from a historiographical perspective. In the first instance, reference is made, in a general way, to the attention that researchers in the history of education have paid to the university environment. For this, analysing academic meetings and historical-educational publications is privileged, understanding that the matter that arouses our attention goes beyond that limited scope. Subsequently, a specific thematic perspective is proposed to illustrate the potential offered by the field of study about the university world (student movements). It is taken as a space to discuss possible new axes of analysis that find themselves more closely aligned with recent academic and political concerns.